Differential Diagnosis of Diarrhea in Patients With Neuroendocrine Tumors. Issue 9 (October 2020) - Eads, Jennifer R.; Reidy-Lagunes, Diane; Soares, Heloisa P.; Chan, Jennifer A.; Anthony, Lowell B.; Halfdanarson, Thorvardur R.; Naraev, Boris G.; Wolin, Edward M.; Halperin, Daniel M.; Li, Daneng; Pommier, Rodney F.; Zacks, Jerome S.; et al.
Abstract : Abstract: Patients with neuroendocrine tumors (NETs) and carcinoid syndrome experience diarrhea that can have a debilitating effect on quality of life. Diarrhea also may develop in response to other hormonal syndromes associated with NETs, surgical complications, medical comorbidities, medications, or food sensitivities. Limited guidance on the practical approach to the differential diagnosis of diarrhea in these patients can lead to delays in appropriate treatment. This clinical review and commentary underscore the complexity in identifying the etiology of diarrhea in patients with NETs. Based on our collective experience and expertise, we offer a practical algorithm to guide medical oncologists and other care providers to expedite effective management of diarrhea and related symptoms in patients with NETs.